Liposome Bupivacaine Compared to Plain Local Anesthetics to Reduce Postsurgical Pain: An Updated Meta-Analysis of Randomized Controlled Trials - Kendall, Mark C. (Pain Res Treat, 2018)
OBJECTIVE: Peripheral nerve blocks for postoperative analgesia have improved block success, but analgesia efficacy has been limited by the short duration of traditional local anesthetics. The results of randomized trials comparing liposome bupivacaine with conventional local anesthetic formulations (e.g., plain bupivacaine and ropivacaine) have generated conflicting results. This study was conducted to systematically review the effectiveness of analgesic efficacy of liposome bupivacaine infiltration at the surgical site versus plain local anesthetic bupivacaine or ropivacaine in patients undergoing surgery. METHODS: PRISMA statement guidelines were followed. A search of electronic databases National Library of Medicine's PubMed database, Cochrane Database of Systematic Reviews, Embase, and Google Scholar from January 2012 to September 2017 was performed. Among the 1,612 records identified, 9 randomized controlled trials involving 779 patients were eligible for data extraction and meta-analysis. RESULTS: Liposome bupivacaine did not reduce postsurgical pain at rest compared to plain local anesthetics at 24 and 48 hours after surgery. Moreover, liposome bupivacaine did not reduce postoperative opioid consumption at 24, 48, or 72 hours when compared to plain local anesthetics. Liposome bupivacaine did reduce postoperative nausea when compared to plain local anesthetics (P =<0.3). There was no significant difference in hospital length of stay between study groups, the use of plain bupivacaine or ropivacaine, or among orthopedic or nonorthopedic procedures. No manifestations of local anesthetic toxicity were reported. CONCLUSIONS: Our results suggest that liposome bupivacaine does not have an analgesic advantage when compared to plain local anesthetics at the surgical site for patients undergoing surgical procedures.